2000
DOI: 10.1016/s0263-8223(99)00126-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of transverse/interlaminar stresses in laminated composites – a selective review and survey of current developments

Abstract: A review is made on the dierent methods used for the estimation of transverse/interlaminar stresses in laminated composite plates and shells. Both analytical and numerical methods are considered. In numerical methods while the emphasis is given on ®nite element methods, other methods like the ®nite dierence method is also brie¯y discussed. Aspects considered are: eects of variation in geometric and material parameters, transverse shear and normal deformation, interface stress continuity and the interfacial bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
109
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(110 citation statements)
references
References 96 publications
1
109
0
Order By: Relevance
“…The simplest approach is based on using Classical Laminated Plate Theory (CLPT). While, CLPT assumes a state of plane stress within each lamina of a multi-directional laminate, interlaminar stresses are most commonly obtained by integrating the three-dimensional equilibrium equations of elasticity through the thickness [1,2]. Nonetheless, three dimensional stress states cannot, in general, be accurately analysed, and three dimensional theories are required for acceptable accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest approach is based on using Classical Laminated Plate Theory (CLPT). While, CLPT assumes a state of plane stress within each lamina of a multi-directional laminate, interlaminar stresses are most commonly obtained by integrating the three-dimensional equilibrium equations of elasticity through the thickness [1,2]. Nonetheless, three dimensional stress states cannot, in general, be accurately analysed, and three dimensional theories are required for acceptable accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in regions such as free edges and regions of stress concentration where the basic assumptions of CLPT are no longer valid. Transverse shear stresses are directly accounted for in the First Order Shear Deformation Plate Theory and higher order theories [2,3]. These Equivalent Single Layer (ESL) theories have limited accuracy in predicting interlaminar stresses because of their failure to account for both Zig-Zag effects (rapid change of slope across layer interfaces due to through the thickness discontinuity of mechanical properties) of the displacement fields in the thickness direction and interlaminar continuity of the transverse stress field [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain the principle of continuous uniform deformation theory the plies are bounded perfectly and the continuity conditions constrained by the Lagrange multipliers to satisfy the boundary conditions in terms of in-plane and flexural displacements. Using the above approach, the in plane and flexural stresses can be easily analyzed in each layer of the lamina [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) finite element models are of course the most natural option, but their computational cost is prohibitive for iterative design studies as many elements are required through the thickness of each layer to obtain accurate stress results [3]. Computationally more efficient models include closed-form solutions based on first-order shear deformation theory [10,11], but these models do not account for higher-order terms and are therefore less accurate for thicker laminates or when layerwise anisotropy of the laminate increases [12]. Kress et al [13] suggested a model to analyze radial stresses in relatively thick curved laminates, and this model was later improved by Roos and Kress [14] to account for interlaminar shear stresses.…”
Section: Introductionmentioning
confidence: 99%